Exploring urban infrastructure challenges in informal peri-urban Woldia: barriers, implications, and informal strategies - Baye, Fentaw (Frontiers in Sustainable Resource Management, 2025)
This study investigates the challenges and inequities in infrastructure provision and service accessibility in informal peri-urban settlements, focusing on Woldia, Ethiopia. Using mixed methods, including survey questionnaires, interviews, focus groups, and field observations, the research explores the interplay between formal policies and informal practices in delivering basic infrastructure such as water, roads, and electricity. Findings reveal systemic exclusion of informal settlements from formal infrastructure planning and investment, perpetuating socio-economic inequalities. Local authorities prioritize planned urban areas, while informal residents rely on alternative, often costlier, and lower-quality services, such as informal water vendors and shared electricity connections. Informal settlers pay exorbitant rates for water—up to 1,645% higher than formal residents—and face unreliable electricity, leading to reliance on firewood and kerosene. Informal actors, including local leaders, vendors, and corrupt officials, play crucial roles in filling service gaps but exacerbate financial burdens. The study underscores the structural neglect of informal settlements, evidenced by stark disparities in investment and infrastructure access between central and peripheral areas. Recommendations include improving municipal accountability, optimizing resource distribution systems, and recognizing the role of non-state actors in service delivery. Addressing these challenges is critical for fostering equitable urban development and improving living conditions in marginalized peri-urban communities. The findings have broad implications for policy reforms aimed at inclusive infrastructure planning and socio-economic equality.